The Importance of the Portfolio Assessment Model to Improve Student’s Self-Regulated Learning - Defika Putri Nastiti; Sigit Santoso; Sudiyanto Sudiyanto (UM Purwokerto Press, 2022)
The purpose of this research is to develop a portfolio assessment model to increase the self-regulated learning of students. With this product, it is hoped that it can become a reference for transformation from traditional assessments to increase self-regulated learning and achieve good learning outcomes. This research is development research to produce a product portfolio model. The results of the research that has been done, show that teachers at MAN 1 Bandar Lampung have difficulty in assessing the appropriate assessment for students and self-regulated learning students. Teachers have not been able to assess things other than traditional assessments, which only judge from the results and results of the exam so that students can evaluate the learning and assessments that have been done. This condition also affects the low self-regulated learning of students from students who rarely archive what has been given by the teacher. The portfolio assessment model has not been implemented in schools so that teachers and students expect a portfolio model so that it can increase the self-regulated learning of students. This research produces a portfolio assessment model and shows a very well-designed and relevant portfolio assessment model in economics learning.